PARADOKS PENERAPAN GOOD GOVERNANCE DI INDONESIA: SUATU TINJAUAN KRITIS MP3EI - Rivai, Aspin Nur Arifin; Bastari, Gema Ramadhan (JPP (Jurnal Politik Profetik), 2019)
This paper explained how harmful the implementation of good governance has been to the well-being of Indonesian people. The concept of good governance starts as a prescription from international finance institution to fix the economic condition of developing state and bring them towards prosperity. On recent developments, good governance has instead become an instrument of control to dictate the policy-making of developing state. This paper argued that good governance actually represents neoliberalism agenda which seeks to engineer the economic landscape of a certain country so it can be more compatible to the needs of global market. This would be proven by problematizing the concept of good governance as well as analysis on the definition of good governance provided by five of its main proponents: UN, UNDP, IMF, World Bank and OECD. Further evidence will be shown through case study in the implementation of Masterplan for Acceleration and Expansion of Indonesia’s Economic Development (MP3EI) which was made in the name of commitment to good governance principle. This paper found that the implementation MP3EI was only advantageous for businessmen and big corporates but tormenting the people of Indonesia. This was a paradox since good governance which is supposed to make a prosperous state instead tormenting the people that should be the state’s main constituent.